Urbanização costeira e sombreamento na praia de Boa Viagem, Recife-PE, Brasil - Rodrigo Mikosz Gonçalves; Admilson da Penha Pacheco; Elmo Leonardo Xavier Tanajura; Luciana Maria da Silva (Revista de Geografía Norte Grande, 2013)
Part of the urban concentration at Recife municipality, capital of Pernambuco State, in Northeastern Brazil is inserted into the coastal zone. Recife according to the census data from 2010 has a population of 1.536.934 inhabitants, distributed in an area of approximately 220 km2. This study aims to investigate the evolution of land use in an area located at Boa Viagem beach (Recife/Pernambuco/Brazil), where was realized a quantitative analysis of land use and urban zone evolution considering aspects of the years 1974, 2005, 2010 and 2011. For this purpose, were used satellite images of high spatial resolution, orthophotos and conducted a survey. The results are quantitative information that characterizes some temporal aspects of coastal zoning in Boa Viagem. Another important result was the identification of shading in a stretch of beach and the determination of shoreline position in the selected area and the comparison with the Coastal Management Act of Pernambuco State.